Answer:
y= -
x +7
Explanation:
y=3x−6
1. to find the gradient of a perpendicular line we find the reciprocal of the original gradinet
so the reciprocal of 3 is -
(we can check this by multiplying both the gradient and seeing if we get -1 -
x 3= -1 )
so the gradient is -
2. we sub in the gradient -
into the equation y=mx+c this give us
y= -
x +c
3. to find the value of c we substitute in the coordinates (we then expand the brackets and then get c on its own)
y= -
x +c
10= -
(-9) +c
10=3+c
7=c
4. we sub in 7=c back to the equation y= -
x +c this gives us
y= -
x +7
5. so our final answer is
y= -
x +7